Titanium surfaces with biomimetic topography and copper incorporation to modulate behaviors of stem cells and oral bacteria - Li, Ruiying; Li, Shuigen; Zhang, Yi; Jin, Di; Lin, Zhiming; Tao, Xian; Chen, Tianlai; Zheng, Liyuan; Zhang, Zhisheng; Wu, Qianju (Frontiers in Bioengineering and Biotechnology, 2023)
Purpose: Insufficient osseointegration and implant-associated infection are major factors in the failure of Ti-based implants, thus spurring scientists to develop multifunctional coatings that are better suited for clinical requirements. Here, a new biomimetic micro/nanoscale topography coating combined with antibacterial copper was simultaneously designed for Ti-based implant surfaces by adopting a hybrid approach combining plasma electrolytic oxidation and hydrothermal treatment. Results: The biological interactions between this biofunctionalized material interface and stem cells promoted cellular adhesion and spreading during initial attachment and supported cellular proliferation for favorable biocompatibility. Bone marrow mesenchymal stem cells (BMMSCs) on the coating displayed enhanced cellular mineral deposition ability, higher alkaline phosphatase activity, and upregulated expression of osteogenic-related markers without the addition of osteoinductive chemical factors, which improved osseointegration. More interestingly, this new coating reduced the viability of oral pathogens (Fusobacterium nucleatum and Porphyromonas gingivalis)—the primary causes of implant-associated infections as indicated by damage of cellular structures and decreased population. This is the first study investigating the antibacterial property of dental implants modified by a hybrid approach against oral pathogens to better mimic the oral environment. Conclusion: These ﬁndings suggest that biofunctionalization of the implant coating by surface modification methods and the incorporation of antibacterial copper (Cu) offer superior osteogenesis capability and effective antibacterial activity, respectively. These strategies have great value in orthopedic and dental implant applications.